The Concept of Countering Material Law (Materiele Wederrechtelijk) And Its Relevance To The Natural Law Stream - Muammar, Muammar (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The development of the concept of unlawfulness (wederrechtelijk) is interesting to accentuate, because unlawful is not only limited to unlawful in the formal sense, but also includes unlawful material law (materiele wederrechtelijk) which has abstract content, because unlawful material law can be interpreted even though the act does not violate the rules of criminal law.Purposes of the Research:  This paper aims to analyze how the relevance of the concept against material law (materiele wederrechtelijk) with the natural law stream that is in line and has an identity between the two.Methods of the Research: This paper uses a type of normative legal research. The approaches used in this paper are the conceptual approach, the theoretical approach, and the philosophical approach.Findings of the Research: The concept of material law is interpreted as not only violating the applicable legal rules. However, this is because an act is considered "against the law" from its origin. This means that the common sense of the community views the act as reprehensible, evil, and immoral. Violating material law is not always interpreted as violating written rules, it can be that the act is not written, but it is considered unlawful (against the law). In that position, the natural law stream became the foothold for the establishment of the concept against material law. Because the natural law school that builds its main thesis on lex naturalist always makes the principles of truth and justice the main benchmark in determining actions between good and bad, evil and not evil, and morals and immorality.